Enhancing HepG2 cell apoptosis with a combined nanoparticle delivery of miR-128–3p agomir and Oroxin B: A novel drug delivery approach based on PI3K-AKT and VEGF pathway crosstalk - Hechen Wang; Xudan Shen; Jiatong Liu; Xinlan Zhu; Su Zeng; Sheng Cai (Asian Journal of Pharmaceutical Sciences, 2025)
Hepatocellular carcinoma (HCC) shows the highest morbidity among liver cancers which is characterized by genetic mutations in hepatocytes, leading to uncontrolled cell growth and proliferation. Current treatment include surgery, chemotherapy and immunotherapy; however, chemotherapeutics, which focus on single-targeted drug therapy, are still associated with certain limitations and may affect the treatment outcomes. Natural products also show the anticancer effect of HCC and hypotoxicity, but overall low activity of natural products limits their further application. miRNAs can modulate post-transcriptional functions of target genes. An increasing body of evidence has demonstrated that miRNAs are the key regulators in HCC by targeting different molecules in different signaling pathways. However, miRNAs are fragile and liable to catabolism by RNases in serum and other body fluids, and small molecules separated from natural products may have limited bio-availability. A chitosan based, targeted, sustained-release nanoparticle delivery miR-128–3p agomir (NA-miR-128–3p) was developed in this work. This nanoparticle was prepared by pentasodium tripolyphosphate (TPP), chitosan hydrochloride and miR-128–3p agomir with target aptamer which was loaded into the chitosan nanoparticle by self-assembly. It can intervene in HCC progress by affecting AKT1 expression. Based on this, a novel, efficient, long-acting, multi-mechanism and low-dosage combination drug delivery strategy was proposed in this work and showed a prominent anti-tumor effect. NA-miR-128–3p combined with natural product Oroxin B significantly affected HCC progression by the interference with VEGF and PI3K-AKT pathways, better than using NA-miR-128–3p and Oroxin B alone. Taken together, this nanoparticle and combinative administration compensate for the shortcomings of the fragile RNA drugs and the low activity of natural products, with high prospects in HCC treatment.